2017
DOI: 10.5001/omj.2017.81
|View full text |Cite
|
Sign up to set email alerts
|

Giant Submandibular Calculus Eroding Oral Cavity Mucosa

Abstract: Sialolithiasis is the formation of calculi or sialoliths in the salivary gland. It is the most common benign condition of the salivary gland. Sialolithiasis can occur in all salivary glands. The submandibular gland is most commonly affected followed by the parotid gland. Calculi commonly measure less than 10 mm. Calculi of more than 15 mm are termed giant salivary gland calculi and are infrequently reported in the literature. Here, we report a case of unusually large submandibular gland calculus of 5 cm in gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 10 publications
0
20
0
3
Order By: Relevance
“…Salivary stasis, ductal inflammation, and injury promote aggregation of mineralized debris to form nidus, which ultimately initiates the formation of sialolith. [13] A number of factors are believed to be responsible in the development and growth of salivary stones in submandibular gland tissues: Wharton's duct is wider and longer than Stenson's duct, the direction of salivary flow in the submandibular duct system is in opposition to that of the force of gravity, submandibular saliva is more alkaline compared with that of the parotids, the submandibular gland secretion comprises a higher amount of mucin proteins, whereas the parotid gland secretion is totally serous, and calcium and phosphate content in submandibular saliva are greater than that in other glands. [14] Based on 120 submandibular gland sialendoscopy studies, Marchal, et al (2001), observed the presence of a sphincter system in the first 3 cm of Wharton's duct in 90% of the cases and proposed that variation of such sphincter-like mechanism within the salivary ducts could be responsible for easier retrograde movement of oral materials.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Salivary stasis, ductal inflammation, and injury promote aggregation of mineralized debris to form nidus, which ultimately initiates the formation of sialolith. [13] A number of factors are believed to be responsible in the development and growth of salivary stones in submandibular gland tissues: Wharton's duct is wider and longer than Stenson's duct, the direction of salivary flow in the submandibular duct system is in opposition to that of the force of gravity, submandibular saliva is more alkaline compared with that of the parotids, the submandibular gland secretion comprises a higher amount of mucin proteins, whereas the parotid gland secretion is totally serous, and calcium and phosphate content in submandibular saliva are greater than that in other glands. [14] Based on 120 submandibular gland sialendoscopy studies, Marchal, et al (2001), observed the presence of a sphincter system in the first 3 cm of Wharton's duct in 90% of the cases and proposed that variation of such sphincter-like mechanism within the salivary ducts could be responsible for easier retrograde movement of oral materials.…”
Section: Discussionmentioning
confidence: 99%
“…Some will experience xerostomia and infrequently the sensation of a gritty, sand-like foreign body in their mouth. [13] The exact etiology of sialolithiasis is unclear. Salivary stasis, ductal inflammation, and injury promote aggregation of mineralized debris to form nidus, which ultimately initiates the formation of sialolith.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations